Digital Comics Based on Local Wisdom: An Innovative Approach to Enhancing Elementary School Students' Reading Comprehension - Kusmajid; Nani Solihati; Siti Zulaiha (Jurnal Pedagogi dan Pembelajaran, 2024)
The low level of students' reading comprehension and literacy is caused by the less than optimal use of innovative learning media. This study aims to analyze the need for the development of digital comics based on local wisdom as a learning medium that can improve the understanding and interest in reading of elementary school students. This study is part of the needs analysis stage in research and development (Research and Development) using the Design Thinking model. Data collection was carried out through interviews, observations and questionnaires distributed to teachers and students, then analyzed using thematic analysis. The results of the study showed that students were very interested in using digital comics as a learning medium. Most students said that digital comics make learning more fun and interesting compared to regular textbooks. In addition, students appreciate the flexibility of digital comics that can be accessed via devices such as cellphones or laptops. Additional features such as animation, sound effects, or the ability to enlarge image details are also attractions that make students more enthusiastic about using digital comics. The conclusion of this study is that the development of digital comics based on local wisdom is very much needed to improve students' understanding and motivation in learning Indonesian in elementary schools.